Rancangan Dan Konfıgurası Jarıngan Pada PT. Samudera Idola Rahayu - Haeruddin Haeruddin; Efendi Efendi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
A computer network is a very important requirement in a company, a network that is not managed will reduce the level of security and function of the network. The importance of management on the internet network in an agency so that the network that is created is centralized or well managed. The author uses Mikrotik to manage networks in companies that have 2 different providers and combine networks using a bridge and DHCP server as a configuration that will be applied and if one of the networks has problems, one of the internet providers can be a network backup. The author uses the Network Development Life Cycle (NDLC) method as a network design flow, the stages of the Network Development Life Cycle (NDLC) method that the author uses include several stages such as: Analysis, Design, Implementation, Monitoring the following stages will be the author's stage in designing the network. By using the Network Development Life Cycle (NDLC) method, it can make it easier for the author to determine the stages that will be carried out by the author